Use of instrumented mouthguards for rugby collisions quantification: a preliminary study on elite players - Petetin, M.; Valdes-Tamayo, L.; Provot, T.; Kneblewski, A.; Rouillon, O.; Rouch, P.; Bourgain, M. (ISEA Engineering of Sport 14 Conference, 2022)
Rugby is a worldwide played sport involving dynamics events when players' heads could be exposed to impacts. Those can lead to concussions which may have long term harmful effects on brain. In field, decision on concussion is of high interest but remains complex to manage. Currently, independent medical doctor should take the decision of maintening the supposed concussed player on the field based on the Sports Concussion Assessment Tool (SCAT). This tool is mainly based on subjective parameters [1]. Up to now, developed technologies, such as sensors integrated in a headband or over the skin or instrumented helmets [2] have not been able to quantitatively measure concussion occurrence in-field. Thus, developing a way to help doctors to take a decision based on quantitative criteria (count and severity of collisions) and in-field, would be of interest. To that purpose, instrumented mouthguards (iMG) seem to be a good candidate as they measure both linear and rotational accelerations and velocities. By comparing to the video recording, iMG based study has been shown to be of interest for American football to investigate concussion, but it has not been done for rugby. Thus, the objective of this study was to investigate the feasibility of using instrumented mouthguards for quantifying head impacts during rugby games.